Judicial Review Of Infrigement Of Superman’s Famous Trademarks Rights: A Case Study Of DC Comic Against PT Maxing Makmur - Mahadewi, Kadek Julia; Rama, Bagus Gede Ari; Amalia, Rafika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Well-known trademark infringement is a serious problem that threatens intellectual property rights in the era of globalization. Well-known brands, which have wide recognition in the market, are often the target of infringement by irresponsible parties, which can harm brand owners and consumers. Regulation of Brand Regulation in Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Article 21 regulates trademark registration. Several examples of well-known trademark infringement such as the Supermen case between DC Comic and PT Maxing Makmur experienced trademark problems due to duplication in trademark ownership without considering the existence of Article 21 of the MIG Law. Indonesia adopts a trademark registration system with a constitutive system. The occurrence of a trademark violation makes an article entitled